Pengembangan Karier Pada Karyawan Terhadap Peningkatan Kinerja Karyawan PT. Unilever Tbk - Dimas Prasetya; David Dzaky Prasetyo; Muhammad Aifa Fahreza; Aurannisa Fadia; Syifa Salsabila; Saridawati Saridawati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Career development is the process of improving the performance capabilities of each individual taken by the organization to ensure that each individual in the organization has the right qualifications and experience available when needed. By referring to the work standards that have been set, performance is also interpreted as the result of employee work both in terms of quality and quantity. Career development is one of the variables that affect individual performance, such as motivating employees to do better work. This study aims to do determine the effect of career development on employee performance. This study used the literature research method and field research by distributing questionnaires. The results of this study show that career development has a significant influence on employees, companies are required to pay attentions to career development programs to increase the responsibility of each individual’s duties.